Theoretical Bases of the Use of Programmatic-having a Special Purpose Method (PHSPM) and his Application are in Ukraine - Koriakina, Katerina; Filippova, Elena; Sekerka, Bohuslav (Univerzita Pardubice, 2008)
In the given article there is determination of concept of programmatic-having a special purpose method of planning of budget (PHSPM), essence of this method opens up on the basis of bringing basic advantages over and failings, Project "Reform of local budgets of Ukraine" is examined as a practical example of introduction and distribution of PHSPM at local level taking into account experience of application of method the countries of European Union.
Keywords: budgetary programs; Strategic Planning; profits and charges; analysis, estimation, monitoring of the programs; transparency of budgetary process; program efficiency